REMNANT Î’-CELL-STIMULATIVE AND ANTI-OXIDATIVE EFFECTS OF PERSEA AMERICANA FRUIT EXTRACT STUDIED IN RATS INTRODUCED INTO STREPTOZOTOCIN - INDUCED HYPERGLYCAEMIC STATE - Rao, U. S. M.; Adinew, Bizuneh (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Insulin-stimulative and anti-oxidative effects of Persea americana fruit extract were evaluated using streptozotocin (STZ). Ethanol extract of P. americana in the concentration of 300 mg/kg body weight/rat /day was orally administered to rats introduced into STZ-induced hyperglycaemic state for a period of 30 days. After the treatment with avocado fruit extract, the elevated levels of blood glucose, glycosylated haemoglobin, blood urea and serum creatinine seen in the hyperglycaemic rats, reverted back to near normal. Similarly, significantly decreased plasma insulin and haemoglobin levels went back to near normal after the treatment, suggesting the insulin-stimulative effect of P. americana fruit. Determination of thiobarbituric acid reactive substances (TBARS), hydroperoxides and both enzymatic and non-enzymatic antioxidants, confirmed the anti-oxidative potential of avocado fruit extract which, in turn, might be responsible for its hypoglycaemic potential. Changes in activities of enzymes such as serum aspartate transaminase (AST), serum alanine transaminase (ALT), and serum alkaline phosphatase (ALP) seen in the control and experimental rats, revealed the tissue-protective nature of Persea americana fruits, while all of the analysed biochemical parameters were comparable to those obtained with gliclazide as a standard reference drug.